Short‐ and Long‐Term Changes in Health‐Related Quality of Life with Weight Loss: Results from a Randomized Controlled Trial. Issue 6 (20th April 2018) - Pearl, Rebecca L.; Wadden, Thomas A.; Tronieri, Jena Shaw; Berkowitz, Robert I.; Chao, Ariana M.; Alamuddin, Naji; Leonard, Sharon M.; Carvajal, Raymond; Bakizada, Zayna M.; Pinkasavage, Emilie; Gruber, Kathryn A.; Walsh, Olivia A.; et al.
Abstract : Objective: The objective of this study was to determine the effects of weight loss and weight loss maintenance (WLM) on weight‐specific health‐related quality of life in a 66‐week trial. Methods: Adults with obesity ( N = 137, 86.1% female, 68.6% black, mean age = 46.1 years) who had lost ≥ 5% of initial weight in a 14‐week intensive lifestyle intervention/low‐calorie diet (LCD) program were randomly assigned to lorcaserin or placebo for an additional 52‐week WLM program. The Impact of Weight on Quality of Life‐Lite (IWQOL‐Lite) scale (including five subscales), Patient Health Questionnaire‐9 (depression), and Perceived Stress Scale were administered at the start of the 14‐week LCD program, randomization, and week 52 of the randomized controlled trial (i.e., 66 weeks total). Results: Significant improvements in all outcomes, except weight‐related public distress, were found following the 14‐week LCD program ( P values < 0.05). Improvements were largely maintained during the 52‐week randomized controlled trial, despite weight regain of 2.0 to 2.5 kg across treatment groups. Participants who lost ≥ 10% of initial weight achieved greater improvements in physical function, self‐esteem, sexual life, and the IWQOL‐Lite total score than those who lost < 5% and did not differ from those who lost 5% to 9.9%. Conclusions: Improvements in weight‐specific health‐related quality of life were achieved with moderate weight loss and were sustained during WLM.